Geopolitical Conflicts: The Case of Israeli - Palestinian Conflict (1947 – 2012) - Oluwashakin, Ph.D, Ajinde (Covenant University Journal of Politics and International Affairs, 2017)
In current history, as in the past, many international conflicts could be explained in terms of geopolitical factors. While geopolitical conflicts are raging in several parts of the world, the Israeli-Palestinian conflict has been most significant since the emergence of the modern state of Israel in 1948, resulting from the November 29, 1947 United Nations Resolution 181 adopted for two states creation in Palestine: one Arab, one Jewish. While the Jewish state came into being, the Arab one has remained a confounding issue. Why has the Palestinian state not been actualized? The paper argues that in last sixty-five years, efforts made to actualize the creation of a Palestinian state have suffered unnecessary paralysis due largely to socio-psychological perceptions and diplomatic conundrum between the two sides. The November 29, 2012 UN General Assembly resolution upgrading the Palestinian Authority from UN ―observer‖ to ―non-state member observer‖ status was a significant diplomatic achievement for the Palestinians, but laced with political landmines. But a Palestinian state can be actualized if certain impediments are removed, with honesty of purpose on both sides and the third party mediators.